Остров любви: роман / Р. Кейн ; [перевод с англ. И. С. Дейнеко] - Кейн Р. (Цветы любви, 2004)
Экземпляры: Ф. 4 (20200707) / Инвентарный номер: 39603 / Сис.шифр: 84(4 Вел) / Авт.знак: К 33 / ГРНТИ: 17.82 / ББК: 84(4 Вел)